Global trends, dynamics, and imperatives for strategic development in business education in an age of disruption - Zhuplev, Anatoly, 1948-; Koepp, Robert W., 1966- (Advances in higher education and professional development (AHEPD) book series., 2022)
"This book explores issues and developments in global business education from the perspective of the national and international socio-economic landscape and how engaging in changes and strategic disruptions associated with the Fourth Industrial Revolution and other forces and impacts"--